(untitled) (American & British Studies Annual, 2012)
James Fenimore Cooper’s The Pioneers (1823) is the first of five novels known as The Leatherstocking Tales. Cooper began writing in an effort to meet mounting financial obligations created after poor business decisions made by his brothers, unresolved legal claims against the estate of his father Judge William Cooper and the radical devaluation in land values brought on by the War of 1812. All of this left Cooper wholly financially dependent upon his pen to support himself, his wife and their four young children. Storytelling was an integral link in the spreading of news, the triumphs, and terrors of living on the frontier. Cooper casts his tale against the backdrop of the French and Indian Wars during which Native Peoples experienced repeated land dispossessions as the French and English fought their war. The story of Chingachgook/John Mohegan is one of resistance to intruders, a narrative which involves bloody conflict in the region where the town Templeton was established.